The impact of co‐existing immune‐mediated diseases on phenotype and outcomes in inflammatory bowel diseases. Issue 6 (20th January 2017) - Conway, G.; Velonias, G.; Andrews, E.; Garber, J. J.; Yajnik, V.; Ananthakrishnan, A. N.
Summary: Background: Inflammatory bowel diseases lead to progressive bowel damage and need for surgery. While the increase in prevalence of other immune‐mediated diseases in IBD is well recognised, the impact of this on the natural history of IBD is unknown. Aim: To determine the impact of concomitant immune‐mediated diseases on phenotypes and outcomes in IBD. Methods: Patients with IBD enrolled in a prospective registry were queried about the presence of other immune‐mediated diseases, defined as those where immune dysregulation plays a role in pathogenesis. Demographics and disease‐related information were obtained. Subjects also completed measures of quality of life. Multivariable regression models compared disease phenotype and outcomes of IBD patients with and without other immune‐mediated diseases. Results: The cohort included 2145 IBD patients among whom 458 (21%) had another immune‐mediated disease. There was no difference in CD phenotype between the two groups. UC patients were more likely to have pancolitis in the presence of another immune‐mediated disease (62%) compared to those without (52%, P  = 0.02). IBD patients with another immune‐mediated disease had higher rates of needing anti‐TNF biologics [Odds ratio (OR) 1.31, 95% CI 1.05–1.63] and surgery (OR 1.26, 95% CI 0.99–1.61). The presence of another immune‐mediated disease was also associated with lower disease‐specific and general physical quality of life. Conclusions: The presence of another immune‐mediated disease in IBD patients was associated with higher likelihood of pancolonic involvement in UC, and a modest increase in need for IBD‐related surgery and anti‐TNF biological therapy. Such patients also experienced worse quality of life. Abstract : Linked Content This article is linked to Vegh et al and Ananthakrishnan papers. To view these articles visithttps://doi.org/10.1111/apt.13987 andhttps://doi.org/10.1111/apt.13998 .